COVID-19 팬데믹 전후 서울시 공공자전거 이용 행태 변화 분석 - 고혜원; Hyewon Goh; 김화환; Hwahwan Kim; 이태수; Taesoo Lee; 송예나; Yena Song (한국경제지리학회지, 2024)
본 연구는 서울시 공공자전거 시스템 ‘따릉이’ 이용 패턴의 시공간적 변화를 분석하여 도시에서 일상적 통행수단으로서 자전거의 가능성을 분석하였다. 자전거는 친환경 교통수단으로 주목 받고 있으며, COVID-19 이후 이용률이 전 세계적으로 증가하여 도시 내에서 교통수단으로서의 가능성도 확대되었다. 본 연구는 2019년, 2021년, 2023년 시간대별 공공자전거 이용량을 분석하고, 이를 시각화하여 이용 패턴 변화를 확인하였다. 그 결과, 공공자전거 이용은 꾸준히 증가하고 있으며 평일 출퇴근 시간대와 상업·업무 지역에서 집중되는 경향이 나타났다. 본 연구는 공공자전거 서비스 발전을 위한 기초 자료로 활용될 수 있으며, 지속가능한 교통수단으로서 자전거의 중요성과, COVID-19와 같은 사회 변화가 교통 수요에 미치는 영향을 이해하는 데 기여할 것이다. This study examined the spatio-temporal changes in usage patterns of the Seoul public bicycle system, ‘Ttareungyi’, to explore the viability of bicycles as a mode of daily utility travels in urban areas. Bicycles have gained attention as an eco-friendly transportation option, and their usage has increased since the COVID-19 pandemic, thereby expanding their role as a viable utility travel mode. The study analyzes public bicycle usage around COVID-19 pandemic period, more specifically years of 2019, 2021, and 2023, and visualizes usage patterns to identify changes in usage behavior. The findings indicate a consistent rise in bicycle usage, with significant concentration during weekday commuting hours and in commercial and business district. The results suggest that public bicycles are increasingly being adopted, particularly in areas with high employment and dense commuter traffic. This study provides valuable data for the development of public bicycle services and contributes to understanding how societal changes, such as the COVID-19 pandemic, impact transportation demand. Furthermore, the research underscores the critical role of integrating bicycles into urban mobility systems to improve connectivity, efficiency, and sustainability in transportation networks.